Doped yttrium lithium fluoride crystal and preparation method thereof

By combining modified polytetrafluoroethylene and ball milling process, the problem of oxide impurity generation caused by contact between water and oxygen at high temperature of yttrium fluoride lithium crystals was solved, and the 2.7-doped yttrium fluoride lithium crystals were significantly improved. The fluorescence emission intensity of μm band is suitable for high-efficiency mid-infrared laser devices.

CN119320981AInactive Publication Date: 2025-01-17ANHUI CRESTRON CRYSTAL MATERIALS CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411447629.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing yttrium lithium crystals are prone to adsorb moisture and oxygen at high temperatures, resulting in the generation of oxide impurities and affecting their performance. Especially in the application of laser devices in the mid-infrared 2.7μm band, there is a lot of room for improvement in performance.

Method used

Modified polytetrafluoroethylene is used to introduce carboxyl groups through gamma ray irradiation and ultrasonic oscillation to improve its affinity to water and oxygen, and control the particle size of raw material powder in combination with the ball milling process, and strictly control the reaction conditions in the crucible drop method. High purity Er and Yb doped yttrium lithium crystals were prepared.

Benefits of technology

It significantly enhances the fluorescence emission effect and fluorescence emission intensity of the 2.7μm band, reduces the generation of oxide impurities, improves the purity and performance of the crystal, and is suitable for efficient mid-infrared laser devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005088143890000091
    Figure BDA0005088143890000091
  • Figure BDA0005088143890000101
    Figure BDA0005088143890000101
Patent Text Reader

Abstract

The invention discloses a doped yttrium lithium fluoride crystal and a preparation method thereof, and belongs to the technical field of crystal preparation, and the preparation method comprises the following steps: S1, weighing L F, YF3, ErF3, YbF3 and modified polytetrafluoroethylene, mixing, and carrying out ball milling to obtain raw material powder; s2, the raw material powder is placed in a tubular resistance furnace, air is exhausted through high-purity nitrogen, the temperature is 750-815 DEG C, HF gas is introduced, a reaction is conducted for 1-5 h, and crystal powder is obtained; s3, the crystal powder is placed in a grinder to be ground into powder, then the powder is placed in a platinum crucible to be compacted, the crucible is sealed, the sealed platinum crucible is placed in a crucible descent crystal growth furnace, the crystal is grown through a crucible descent method, and the doped yttrium lithium fluoride crystal is obtained.The obtained doped yttrium lithium fluoride crystal is higher in 2.7-micron fluorescence intensity, suitable for laser devices and capable of being used for laser devices. And high-efficiency mid-infrared light laser of 2.7 microns is output.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of crystal preparation, and in particular relates to a yttrium fluoride-doped lithium crystal and a preparation method thereof. Background Art

[0002] In recent years, the development characteristics of solid lasers have shown diversified and multi-wave optical properties, and have become one of the research hotspots of laser crystals. Yttrium lithium fluoride crystals (YLF) have excellent material properties and spectral characteristics. When doped with various rare earth ions and sensitizing ions, laser transitions in multiple bands from ultraviolet 0.3μm to mid-infrared 3.9μm can be obtained. It is a high-efficiency laser working material that is compatible with many important laser reactions at room temperature.

[0003] Due to its important applications in laser medical surgery, remote sensing, lidar, chemical sensing, air pollution control, communications and military, solid-state lasers in the mid-infrared 2.7μm central band have received great attention from research institutions at home and abroad.

[0004] The Chinese patent with the authorization publication number CN102978701 B discloses an Er 3+ / Yb 3+ Co-doped lithium yttrium fluoride single crystal and preparation method thereof, mainly comprising Li F, YF 3 ,ErF 3 , YbF 3 Made of materials, due to Er 3+ With Yb 3+ The segregation coefficients are all close to 1, and they can output high-efficiency 2.7μm mid-infrared lasers. Their high transmittance in the mid-infrared makes them more suitable for applications in laser devices. However, due to the presence of water vapor in the environment, fluoride raw materials are prone to absorb moisture and hydrolyze at high temperatures. At the same time, they are also prone to generate oxide impurities and form oxygen pollution, resulting in the final co-doped lithium yttrium fluoride single crystal. There is still much room for improvement in performance. Summary of the invention

[0005] The object of the present invention is to provide a doped lithium yttrium fluoride crystal and a preparation method thereof, so as to obtain high-performance co-doped lithium yttrium fluoride crystal.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A method for preparing a lithium yttrium fluoride-doped crystal comprises the following steps:

[0008] S1. Weigh Li F, YF 3 ,ErF 3 , YbF 3 and modified polytetrafluoroethylene, and then placed in a ball mill, adding steel ball media, and grinding to an average particle size of 3.5-6.5 μm to obtain a raw material powder;

[0009] S2, placing the raw material powder in a platinum crucible, then placing the platinum crucible in a tubular resistance furnace, exhausting the air with high-purity nitrogen, then raising the furnace temperature of the tubular resistance furnace to 750-815°C, passing HF gas, reacting for 1-5h, absorbing HF gas in the tail gas with sodium hydroxide solution during the reaction, stopping passing HF gas after the reaction, closing the tubular resistance furnace, and exhausting the residual HF gas in the platinum pipeline with high-purity nitrogen to obtain crystalline powder;

[0010] S3, grinding the crystal powder into powder in a grinder, and then placing it in a platinum crucible for compaction, sealing the crucible, placing the sealed platinum crucible in a crucible descent crystal growth furnace, and growing crystals by a crucible descent method to obtain doped yttrium lithium fluoride crystals.

[0011] Furthermore, LiF, YF 3 ,ErF 3 and YbF 3 The molar percentage is 51.5:38.5-47.0:1-4:0.5-6, and the amount of modified polytetrafluoroethylene is Li F, YF 3 ,ErF 3 and YbF 3 The mass and 0.1-0.3%.

[0012] Furthermore, the ball mill speed is 200-300 r / min, and the material-ball ratio is 1:8-12.

[0013] Furthermore, LiF, YF 3 ,ErF 3 and YbF 3 The purity is 99.999%.

[0014] Furthermore, the modified polytetrafluoroethylene is acrylic acid grafted polytetrafluoroethylene.

[0015] Further, the modified polytetrafluoroethylene is prepared by the following steps:

[0016] Take polytetrafluoroethylene powder and put it into a polyethylene bag. 60 Co source gamma rays were irradiated in air for 50 kGy to obtain pre-irradiated polytetrafluoroethylene;

[0017] Pre-irradiated polytetrafluoroethylene was placed in a conical flask, and acrylic acid, anhydrous ethanol, distilled water, ammonium ferrous sulfate and concentrated sulfuric acid were added. Ultrasonic oscillation was performed for 3 minutes. After nitrogen was passed for 20 minutes, the flask was sealed and heated to 60°C in a water bath for reaction for 2-3 hours. The flask was filtered and the product was wrapped with filter paper and extracted with deionized water in a Soxhlet extractor for 60 hours to remove residual acrylic acid and homopolymer. The product was dried to obtain modified polytetrafluoroethylene.

[0018] Furthermore, the usage ratio of pre-irradiated polytetrafluoroethylene, acrylic acid, anhydrous ethanol, distilled water, ammonium ferrous sulfate and concentrated sulfuric acid is 5g:50mL:30mL:20mL:20-40mg:50uL, and the mass fraction of concentrated sulfuric acid is 95%.

[0019] After γ-ray irradiation, polytetrafluoroethylene powder generates trapped free radicals and peroxides, which are activated by heating to trigger the grafting reaction of acrylic acid, introduce carboxyl groups on the surface of polytetrafluoroethylene powder, and improve the affinity of polytetrafluoroethylene with water and oxygen.

[0020] Furthermore, the average particle size of the polytetrafluoroethylene powder is 5 μm.

[0021] Furthermore, the purity of the high-purity nitrogen is greater than 99.999%.

[0022] Furthermore, the specific steps of growing crystals by the crucible descent method are as follows:

[0023] The parameters for growing crystals are: furnace vacuum degree is 10 -3 Pa, furnace temperature is 920-980℃, inoculation temperature is 820-850℃, temperature gradient of solid-liquid interface is 25-55℃ / cm, crucible descending speed is 1.5-2.5mm / h, descending height is 100mm, after crystal growth is completed, furnace temperature is lowered to room temperature at 30-70℃ / h.

[0024] Furthermore, the ratio of the diameter of the heater to the diameter of the platinum crucible in the crucible descent crystal growth furnace is 4:1.

[0025] A yttrium fluoride-doped lithium crystal is prepared by the above preparation method.

[0026] Beneficial effects of the present invention:

[0027] The present invention provides a doped lithium yttrium fluoride crystal, specifically an Er and Yb doped lithium yttrium fluoride crystal, which has a greatly enhanced fluorescence emission effect of 2.7um compared with an undoped lithium yttrium fluoride crystal, and compared with the existing preparation method of Er and Yb doped lithium yttrium fluoride crystal, the obtained Er and Yb doped lithium yttrium fluoride crystal has a stronger fluorescence emission intensity at 2.7um, and the specific reasons include the following points:

[0028] First, the present invention introduces modified polytetrafluoroethylene in the process of preparing raw material powder. The surface of the modified polytetrafluoroethylene contains more carboxyl groups and has a higher affinity for water and oxygen. In the process of grinding the fluoride raw material, it preferentially adsorbs oxygen and water vapor in the air, reduces the contact between the fluoride raw material and water and oxygen, significantly reduces the subsequent generation of oxide impurities, and ensures the purity of the polycrystalline raw material; in addition, in the process of preparing the crystal powder, the modified polytetrafluoroethylene can react with trace oxygen impurities to produce carbon dioxide, further improving the purity of the raw material, and completely decomposes at high temperature; the preparation of high-purity polycrystalline raw materials is conducive to obtaining high-performance doped lithium yttrium fluoride crystals;

[0029] Second, the present invention strictly controls the particle size of the raw material powder. If the raw material powder particles are too small, the surface area is larger, and it is easier to react with water. If the raw material powder particles are too large, it is easy to cause incomplete reaction. Therefore, the present invention controls the average particle size of the raw material powder to 3.5-6.5 μm through the ball milling process, and the obtained doped lithium yttrium fluoride crystal has higher performance;

[0030] Thirdly, the present invention strictly controls the dosage range of modified polytetrafluoroethylene, specifically, LiF, YF 3 ,ErF 3 and YbF 3 The weight of the raw material is 0.1-0.3%. Too low a dosage will lead to poor deoxygenation effect and reduced purity of the crystal powder. Too high a dosage will lead to excessive decomposition products remaining in the system, forming a new source of pollution, resulting in reduced purity of the crystal powder, and further affecting the final performance of the doped lithium yttrium fluoride crystal. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Preparation Example 1

[0033] A modified polytetrafluoroethylene is prepared by the following steps:

[0034] Take 50g of polytetrafluoroethylene powder and put it into a polyethylene bag. 60 Co source gamma rays were irradiated in air for 50 kGy to obtain pre-irradiated polytetrafluoroethylene;

[0035] 5 g of pre-irradiated polytetrafluoroethylene was placed in a conical flask, and 50 mL of acrylic acid, 30 mL of anhydrous ethanol, 20 g of distilled water, 20 mg of ammonium ferrous sulfate and 50 uL of concentrated sulfuric acid were added, with the mass fraction of concentrated sulfuric acid being 95%. Ultrasonic oscillation was performed for 3 min, nitrogen was passed through for 20 min, and then the flask was sealed. The flask was heated to 60 ° C in a water bath and reacted for 2 h. The flask was filtered, and the product was wrapped with filter paper and extracted with deionized water in a Soxhlet extractor for 60 h to remove residual acrylic acid and homopolymers. The product was dried to obtain modified polytetrafluoroethylene.

[0036] The average particle size of polytetrafluoroethylene powder is 5 μm and it comes from Zhejiang Shenjia Technology Co., Ltd.

[0037] Preparation Example 2

[0038] A modified polytetrafluoroethylene is prepared by the following steps:

[0039] Take 50g of polytetrafluoroethylene powder and put it into a polyethylene bag. 60 Co source gamma rays were irradiated in air for 50 kGy to obtain pre-irradiated polytetrafluoroethylene;

[0040] 5 g of pre-irradiated polytetrafluoroethylene was placed in a conical flask, and 50 mL of acrylic acid, 30 mL of anhydrous ethanol, 20 g of distilled water, 30 mg of ammonium ferrous sulfate and 50 uL of concentrated sulfuric acid were added, with the mass fraction of concentrated sulfuric acid being 95%. Ultrasonic oscillation was performed for 3 min, nitrogen was passed through for 20 min, and then the flask was sealed. The flask was heated to 60 ° C in a water bath and reacted for 2.5 h. The flask was filtered, and the product was wrapped with filter paper and extracted with deionized water in a Soxhlet extractor for 60 h to remove residual acrylic acid and homopolymers, and then dried to obtain modified polytetrafluoroethylene.

[0041] The average particle size of polytetrafluoroethylene powder is 5 μm and it comes from Zhejiang Shenjia Technology Co., Ltd.

[0042] Example 1

[0043] A method for preparing a lithium yttrium fluoride-doped crystal comprises the following steps:

[0044] S1, weigh 51.5 mol of LiF, 47.0 mol of YF 3 , 1mol of ErF 3 , 0.5 mol YbF 3 and the modified polytetrafluoroethylene of Preparation Example 1, wherein the amount of modified polytetrafluoroethylene is Li F, YF 3 ,ErF 3 and YbF 3 The weight of the mixture is 0.1% and 0.1%, and the mixture is placed in a ball mill, and steel ball media is added. The ball mill speed is 200r / min, and the material-ball ratio is 1:8. The mixture is ground to an average particle size of 3.5-6.5μm to obtain a raw material powder.

[0045] S2, placing the raw material powder in a platinum crucible, then placing the platinum crucible in a tubular resistance furnace, exhausting the air with high-purity nitrogen, then raising the furnace temperature of the tubular resistance furnace to 750° C., passing HF gas, and reacting for 5 hours. During the reaction, HF gas in the tail gas is absorbed by sodium hydroxide solution. After the reaction is completed, the HF gas is stopped, the tubular resistance furnace is closed, and the residual HF gas in the platinum pipeline is exhausted with high-purity nitrogen to obtain crystalline powder;

[0046] S3, grinding the crystal powder into powder in a grinder, and then placing it in a platinum crucible for compaction, sealing the crucible, placing the sealed platinum crucible in a crucible descent crystal growth furnace, and growing crystals by a crucible descent method to obtain doped yttrium lithium fluoride crystals.

[0047] Li F, YF 3 ,ErF 3 and YbF 3 The purity is 99.999%.

[0048] The purity of high-purity nitrogen is greater than 99.999%.

[0049] The specific steps of growing crystals by the crucible descent method are:

[0050] The parameters for growing crystals are: furnace vacuum degree is 10 -3 Pa, the furnace temperature is 920℃, the inoculation temperature is 820℃, the temperature gradient of the solid-liquid interface is 25℃ / cm, the crucible descent speed is 1.5mm / h, the descent height is 100mm, and after the crystal growth is completed, the furnace temperature is lowered to room temperature at 30℃ / h.

[0051] The ratio of the diameter of the heater to the diameter of the platinum crucible in the crucible descent crystal growth furnace is 4:1.

[0052] Example 2

[0053] A method for preparing a lithium yttrium fluoride-doped crystal comprises the following steps:

[0054] S1, weigh 51.5 mol of LiF, 38.5 mol of YF 3 , 4mol of ErF 3 、6mol of YbF 3 and the modified polytetrafluoroethylene of Preparation Example 2, wherein the amount of modified polytetrafluoroethylene is Li F, YF 3 ,ErF 3 and YbF 3 The weight of the raw materials is 0.2% and 0.2%, respectively, and the mixture is placed in a ball mill, and steel ball media is added. The ball mill speed is 250r / min, and the material-ball ratio is 1:10. The raw material powder is obtained after grinding to an average particle size of 3.5-6.5μm.

[0055] S2, placing the raw material powder in a platinum crucible, then placing the platinum crucible in a tubular resistance furnace, exhausting the air with high-purity nitrogen, then raising the furnace temperature of the tubular resistance furnace to 800° C., passing HF gas, and reacting for 3 hours. During the reaction, HF gas in the tail gas is absorbed by sodium hydroxide solution. After the reaction is completed, stop passing HF gas, close the tubular resistance furnace, and exhaust the residual HF gas in the platinum pipeline with high-purity nitrogen to obtain crystalline powder;

[0056] S3, grinding the crystal powder into powder in a grinder, and then placing it in a platinum crucible for compaction, sealing the crucible, placing the sealed platinum crucible in a crucible descent crystal growth furnace, and growing crystals by a crucible descent method to obtain doped yttrium lithium fluoride crystals.

[0057] Li F, YF 3 ,ErF 3 and YbF 3 The purity is 99.999%.

[0058] The purity of high-purity nitrogen is greater than 99.999%.

[0059] The specific steps of growing crystals by the crucible descent method are:

[0060] The parameters for growing crystals are: furnace vacuum degree is 10 -3 Pa, the furnace temperature is 960℃, the inoculation temperature is 840℃, the temperature gradient of the solid-liquid interface is 45℃ / cm, the crucible descending speed is 2mm / h, the descending height is 100mm, and after the crystal growth is completed, the furnace temperature is lowered to room temperature at 40℃ / h.

[0061] The ratio of the diameter of the heater to the diameter of the platinum crucible in the crucible descent crystal growth furnace is 4:1.

[0062] Example 3

[0063] A method for preparing a lithium yttrium fluoride-doped crystal comprises the following steps:

[0064] S1, weigh 51.5 mol of LiF, 45.5 mol of YF 3 , 1mol of ErF 3 , 2mol of YbF 3 and the modified polytetrafluoroethylene of Preparation Example 1, wherein the amount of modified polytetrafluoroethylene is Li F, YF 3 ,ErF 3 and YbF 3 The weight of the mixture is 0.3% and 0.3%, and the mixture is placed in a ball mill, and steel ball media is added. The ball mill speed is 300r / min, and the material-ball ratio is 1:12. The mixture is ground to an average particle size of 3.5-6.5μm to obtain a raw material powder;

[0065] S2, placing the raw material powder in a platinum crucible, then placing the platinum crucible in a tubular resistance furnace, exhausting the air with high-purity nitrogen, then raising the furnace temperature of the tubular resistance furnace to 815°C, passing HF gas, and reacting for 1 hour. During the reaction, HF gas in the tail gas is absorbed by sodium hydroxide solution. After the reaction is completed, stop passing HF gas, close the tubular resistance furnace, and exhaust the residual HF gas in the platinum pipeline with high-purity nitrogen to obtain crystalline powder;

[0066] S3, grinding the crystal powder into powder in a grinder, and then placing it in a platinum crucible for compaction, sealing the crucible, placing the sealed platinum crucible in a crucible descent crystal growth furnace, and growing crystals by a crucible descent method to obtain doped yttrium lithium fluoride crystals.

[0067] Li F, YF 3 ,ErF 3 and YbF 3 The purity is 99.999%.

[0068] The purity of high-purity nitrogen is greater than 99.999%.

[0069] The specific steps of growing crystals by the crucible descent method are:

[0070] The parameters for growing crystals are: furnace vacuum degree is 10 -3 Pa, the furnace temperature is 980℃, the inoculation temperature is 850℃, the temperature gradient of the solid-liquid interface is 55℃ / cm, the crucible descent speed is 2.5mm / h, the descent height is 100mm, and after the crystal growth is completed, the furnace temperature is lowered to room temperature at 70℃ / h.

[0071] The ratio of the diameter of the heater to the diameter of the platinum crucible in the crucible descent crystal growth furnace is 4:1.

[0072] Comparative Example 1

[0073] A method for preparing doped lithium yttrium fluoride crystals, compared with Example 1, the difference is that the modified polytetrafluoroethylene in Example 1 is replaced by polytetrafluoroethylene, the average particle size of the polytetrafluoroethylene powder is 5 μm, and it comes from Zhejiang Shenjia Technology Co., Ltd., and the other raw materials and preparation methods are the same as Example 1.

[0074] Comparative Example 2

[0075] A method for preparing yttrium fluoride-doped lithium crystals, compared with Example 1, the difference is that the average particle size of the raw material powder is controlled to be 0.4-3.4 μm through a ball milling process, and the other raw materials and preparation method are the same as Example 1.

[0076] Comparative Example 3

[0077] A method for preparing yttrium fluoride-doped lithium crystals, compared with Example 3, the difference is that the average particle size of the raw material powder is controlled to be 6.7-9.7 μm through a ball milling process, and the remaining raw materials and preparation method are the same as Example 3.

[0078] Comparative Example 4

[0079] A method for preparing lithium yttrium fluoride doped crystals, compared with Example 1, the difference is that the amount of modified polytetrafluoroethylene is controlled to be Li F, YF 3 ,ErF 3 and YbF 3 The mass and the total amount are 0.05%, and the other raw materials and preparation method are the same as those in Example 1.

[0080] Comparative Example 5

[0081] A method for preparing lithium yttrium fluoride doped crystals, compared with Example 3, the difference is that the amount of modified polytetrafluoroethylene is controlled to be Li F, YF 3 ,ErF 3 and YbF 3 The mass ratio is 0.35%, and the other raw materials and preparation method are the same as those in Example 3.

[0082] Comparison example

[0083] A method for preparing a lithium yttrium fluoride-doped crystal comprises the following steps:

[0084] S1, weigh 51.5 mol of LiF, 38.5 mol of YF 3 , 4mol of ErF 3 、6mol of YbF 3 , after mixing, put it in a ball mill, add steel ball medium, the ball mill speed is 200r / min, the material-ball ratio is 1:8, grind to an average particle size of 3.5-6.5μm, and obtain raw material powder;

[0085] S2, placing the raw material powder in a platinum crucible, then placing the platinum crucible in a tubular resistance furnace, exhausting the air with high-purity nitrogen, then raising the furnace temperature of the tubular resistance furnace to 815°C, passing HF gas, and reacting for 1 hour. During the reaction, HF gas in the tail gas is absorbed by sodium hydroxide solution. After the reaction is completed, stop passing HF gas, close the tubular resistance furnace, and exhaust the residual HF gas in the platinum pipeline with high-purity nitrogen to obtain crystalline powder;

[0086] S3, grinding the crystal powder into powder in a grinder, and then placing it in a platinum crucible for compaction, sealing the crucible, placing the sealed platinum crucible in a crucible descent crystal growth furnace, and growing crystals by a crucible descent method to obtain doped yttrium lithium fluoride crystals.

[0087] Li F, YF 3 ,ErF 3 and YbF 3 The purity is 99.999%.

[0088] The purity of high-purity nitrogen is greater than 99.999%.

[0089] The steps of growing crystals by the crucible descent method are the same as those in Example 1.

[0090] The lithium yttrium fluoride doped crystals obtained in Examples 1 to 3 and Comparative Examples 1 to 5 and the reference example were polished into 2 mm thin slices and subjected to fluorescence testing. Specifically, the fluorescence intensity of the lithium yttrium fluoride doped crystals in Examples 1 to 3 and Comparative Examples 1 to 5 at 2.7 um was tested, and the ratio to the fluorescence intensity of the reference example crystal at 2.7 um was calculated. The test results are shown in Table 1:

[0091] Table 1

[0092]

[0093]

[0094] It can be seen from the data recorded in Table 1 that, compared with Comparative Examples 1-5, the yttrium fluoride-doped lithium crystals obtained in Example 1-3 have stronger fluorescence intensity at 2.7um, are suitable for use in laser devices, and output high-efficiency 2.7um mid-infrared lasers.

[0095] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0096] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a doped yttrium fluoride lithium crystal, characterized in that: The following steps are involved: S1. Weigh Li F, YF3, ErF3, YbF3 and modified polytetrafluoroethylene, mix and place in a ball mill, add steel ball medium, grind to an average particle size of 3.5-6.5 μm, and obtain raw material powder; S2, placing the raw material powder in a platinum crucible, then placing the platinum crucible in a tubular resistance furnace, exhausting the air with high-purity nitrogen, then raising the furnace temperature of the tubular resistance furnace to 750-815° C., introducing HF gas, and reacting for 1-5 hours. After the reaction is completed, stop passing the HF gas, close the tubular resistance furnace, and exhaust the residual HF gas in the platinum pipeline with high-purity nitrogen to obtain a crystalline powder; S3, grinding the crystal powder into powder in a grinder, and then placing it in a platinum crucible for compaction, sealing the crucible, placing the sealed platinum crucible in a crucible descending crystal growth furnace, and growing crystals by a crucible descending method to obtain doped yttrium lithium fluoride crystals; Modified polytetrafluoroethylene is acrylic acid grafted polytetrafluoroethylene.

2. The method for preparing a doped yttrium fluoride lithium crystal according to claim 1, characterized in that: The molar percentages of Li F, YF3, ErF3 and YbF3 are 51.5:38.5-47.0:1-4:0.5-6, and the amount of modified polytetrafluoroethylene is 0.1-0.3% of the total mass of Li F, YF3, ErF3 and YbF3.

3. The method for preparing a doped lithium yttrium fluoride crystal according to claim 1, characterized in that: Modified polytetrafluoroethylene is made by the following steps: Take polytetrafluoroethylene powder and put it into a polyethylene bag. 60 Co source gamma rays were irradiated in air for 50 kGy to obtain pre-irradiated polytetrafluoroethylene; Pre-irradiated polytetrafluoroethylene was placed in a conical flask, and acrylic acid, anhydrous ethanol, distilled water, ammonium ferrous sulfate and concentrated sulfuric acid were added. Ultrasonic oscillation was performed for 3 minutes. After nitrogen was passed for 20 minutes, the flask was sealed and heated to 60°C in a water bath for reaction for 2-3 hours. The flask was filtered and the product was wrapped with filter paper and extracted with deionized water in a Soxhlet extractor for 60 hours to remove residual acrylic acid and homopolymer. The product was dried to obtain modified polytetrafluoroethylene.

4. The method for preparing a doped lithium yttrium fluoride crystal according to claim 1, characterized in that: The dosage ratio of pre-irradiated polytetrafluoroethylene, acrylic acid, anhydrous ethanol, distilled water, ammonium ferrous sulfate and concentrated sulfuric acid is 5g:50mL:30mL:20mL:20-40mg:50uL.

5. A lithium yttrium fluoride-doped crystal, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • An Er3+ / Yb3+ co-doped lithium yttrium fluoride single crystal and its preparation method

    CN102978701B

  • Pr / Yb doped yttrium lithium fluoride monocrystal used for modulation of solar spectrum and preparation method thereof

    CN102817076A

  • Er<3+> / Pr<3+> co-doped yttrium lithium fluoride monocrystal and preparation method thereof

    CN102978700A

  • Er<3+> / Yb<3+> co-doped yttrium lithium fluoride monocrystal and preparation method thereof

    CN102978701A

  • Ho<3+> / Pr<3+> codoping lithium yttrium fluoride monocrystal and preparation method thereof

    CN103014854A